Use-Wear Experiment: Identifying the Functions of Palaeolithic People's Flake Tools in Tingkayu, Sabah: (Eksperimen Kesan Guna: Identifikasi Fungsi Alat Repeh Masyarakat Awal Paleolitik Tingkayu, Sabah) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
Archaeological artefacts are a tangible heritage and a part of material culture. Artefacts from the palaeolithic age that are usually found are stone artefacts. These stone artefacts comprise tools, stone tools and work residue. One focus of material culture studies concerning stone artefacts is to determine their function. Determining the functions of stone tools can be achieved through experiments. The results of these experiments will be compared with stone tool artefacts. Attributes resulting from the experiment can be indicators to determine the real functions of stone tool artefacts. The results of the analysis reveal that the flake tools from Tingkayu were used in activities such as sawing, scraping and drilling. This analysis contributes to knowledge concerning the functions of use of tools in Palaeolithic societies, and strengthens as well as adds data on the use-wear of flake tools in Malaysia and Southeast Asia.Keywords: Experiment, Palaeolithic, function, use-wear, flake tools, Tingkayu